Byzantine Intersectionality : Sexuality, Gender, and Race in the Middle Ages - Betancourt, Roland (Princeton University Press, 2020)
Cover -- Title Page -- Copyright Page -- CONTENTS -- Note on the Text -- Introduction -- I The Virgin's Consent -- II Slut-Shaming an Empress -- III Transgender Lives -- IV Queer Sensations -- Color Plate -- V The Ethiopian Eunuch -- Epilogue -- Acknowledgments -- Notes -- Bibliography -- Index -- Photo Credits.